2014
DOI: 10.1038/srep05028
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Acupressure Reduces Anxiety Levels and Improves Outcomes of in Vitro Fertilization: A Prospective, Randomized and Controlled Study

Abstract: The study was to explore whether auricular acupressure (AA) can relieve anxiety during the period from trans-vaginal oocyte retrieval to the embryo transfer in IVF treatment and whether AA can improve the outcomes of IVF. 305 infertile patients with tubal blockage who were referred for IVF were included. The women were randomized into a control group with 102 cases, a Sham-AA group with 102 cases and an AA group with 101 cases. The anxiety levels were rated with Spielberger's State Trait Anxiety Inventory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 58 publications
(58 reference statements)
1
65
0
1
Order By: Relevance
“…A total of 34 studies with 7213 patients overall were included in both the qualitative and the quantitative synthesis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 34 studies with 7213 patients overall were included in both the qualitative and the quantitative synthesis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of infertility was 3.6 years, and the duration was longer than 5 years in 26.4% of the patients. In total, 23 studies reported emotional ratings at baseline . Anxiety, depression, and infertility distress were the most common psychological disorders before the beginning of ART treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential mechanism of auricular stimulation is attributed to the neuroanatomical conditions of external auricle. It is presumed, that auricular stimulation exerts its anxiolytic effects via the involvement of cranial nerves (18), which leads to the modulation of the brain areas involved in the stress response, including the limbic system, locus coeruleus and hypothalamus (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%